HUBUNGAN KUALITAS TIDUR DENGAN KELUHAN MUSKULOSKELETAL PADA STAF UPNVJ TAHUN 2020 - AZZAHRA BRENDA TAM, (2021)
Musculoskeletal disorders (MSDs) have been found around the world. In Indonesia, the prevalence of MSDs that causes disruption of activities reaches 9.2% with office workers complaining pain on the neck by 68%, upper back 62%, and lower back 60%. In developing countries, MSDs are occupational diseases that are mostly found in 40-95% lecturers. In 2020, COVID-19 strikes in Indonesia resulted in the government implementing a work from home (WFH) system which caused 66.3% of workers to start experiencing pain during WFH. This can be caused by not meeting physiological needs, one of which is sleep. It's stated that 41.9% of adults experience sleep disorders which have an effect on musculoskeletal complaints. The objective of this research was to establish the association between sleep quality and musculoskeletal complaints. This is an analytical study using cross sectional technique on the lecturers and teaching staff at FK UPNVJ. A sample of 103 people was taken using purposive sampling. Data were collected using the PSQI for sleep quality and NMQ for musculoskeletal complaints, then distributed online via Google form. The data will be analyzed by univariate and bivariate using SPSS. Based on the analysis, it was showed that most of the respondents were female (54.8%), had poor sleep quality (94%), and experienced musculoskeletal complaints (73.8%). Based on bivariate analysis using the Chi-square test, there was a huge link between the quality of sleep and musculoskeletal complaints (p = 0.016). The low quality of sleep in lecturers and teaching staff increase the risk of developing musculoskeletal disorders.